Chilled Storage Studies of Depurated Cooked Clam Meat in two different Packaging Materials - Sreedevi, K. H.; James, J. P.; Bindu, J.; Sreejith, S.; Gopal, Nikita (Fishery Technology, 2018)
The biochemical and microbiological parameters of depurated cooked meat of black clam (Villorita cyprinoides) (Gray, 1825) was assessed for the extension of shelflife in iced condition in two different packaging materials viz., Polyester polyethylene laminate (PEST-PE) and low density polyethylene (LDPE). Aerobic plate count revealed that the shelflife of black clam was 22 days in PEST-PE and 16 days in LDPE during which the count reached 5.38 log cfug-1 and 4.9 log cfug-1, respectively. The clam meat stored in LDPE had a TBA value of 1.36 mg MDAkg-1 on 16th day and it was 1.23 mg MDAkg-1 for PEST-PE packed meat on the 22nd day. The values of TVB-N was 7.0 mg% and 7.4 mg% after 16 days and 22 days in the LDPE and PESTPE, respectively. Since the value of APC was 5.38 log cfug-1 on the 16th day for clam meat packed in LDPE it was not analysed further as the microbiological count exceeded the limit of acceptability. From this study it is inferred that the shelflife of clam meat may be extended by proper icing after packaging in suitable packing material like PEST-PE.